2014
DOI: 10.1002/ijc.28762
|View full text |Cite
|
Sign up to set email alerts
|

CD24 knockout prevents colorectal cancer in chemically induced colon carcinogenesis and in APCMin/CD24 double knockout transgenic mice

Abstract: Increased expression of CD24 is seen in a large variety of solid tumors, including up to 90% of gastrointestinal (GI) tumors. Stable derivatives of SW480 colorectal cancer (CRC) cells that overexpress CD24 proliferate faster, and increase cell motility, saturation density, plating efficiency, and growth in soft agar. They also produce larger tumors in nude mice as compared to the parental SW480 cells. Most significantly, even depletion of one copy of the CD24 allele in the APCMin/+ mice of a transgenic mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…Immunoblots showed an increase in the Notch pathway inhibitory regulator Numb, and in colonic stem cell markers JAG1 (Jagged-1) (P<0.05), while MSI1 (Musahi-1), and Lgr5 showed a tendency toward increase but the high variance resulted in non-significant P values. In contrast, levels of CD24, a cell adhesion protein involved in leukocyte migration to the colon (42) and a colonic cancer stem cell marker (43), decreased in Sgo1 mice (P<0.05).…”
Section: Resultsmentioning
confidence: 96%
“…Immunoblots showed an increase in the Notch pathway inhibitory regulator Numb, and in colonic stem cell markers JAG1 (Jagged-1) (P<0.05), while MSI1 (Musahi-1), and Lgr5 showed a tendency toward increase but the high variance resulted in non-significant P values. In contrast, levels of CD24, a cell adhesion protein involved in leukocyte migration to the colon (42) and a colonic cancer stem cell marker (43), decreased in Sgo1 mice (P<0.05).…”
Section: Resultsmentioning
confidence: 96%
“…Some of them, such as p53 and COX2, play a critical role in carcinogenesis [20, 21]. It has been confirmed that p53 and COX2 mutations could induce carcinogenesis [4, 14], and COX2 could increase the risk of adenoma recurrence [15]. The mechanisms included inhibiting the apoptosis of cancer cells, promoting tumor angiogenesis, inhibiting the immunity of the organism, and increasing the invasion and metastasis of tumors [22–25] .…”
Section: Discussionmentioning
confidence: 99%
“…In a BBN-induced carcinogenesis mouse model that mimics muscle-invasive human bladder cancer, CD24 knockout mice developed fewer bladder tumors and in mice with cancer, fewer had metastases compared to wild type mice (5). Homozygous deletion of CD24 in APC (Min/+) mice causes complete abolishment of tumor formation in all sections of small intestine (8). Knockdown of CD24 also retards the growth, progression and metastasis of prostate cancer (9), gastric cancer (10), and breast cancer (11).…”
Section: Introductionmentioning
confidence: 99%